Geographical Distribution of Pyrethroid Resistance Allele Frequency in Head Lice (Phthiraptera: Pediculidae) From Argentina - Toloza, Ariel Ceferino (2013)
The human head louse, Pediculus humanus capitis De Geer (Phthiraptera: Pediculidae), is an obligate ectoparasite that causes pediculosis capitis and has parasitized humans since the beginning of humankind. Head louse infestations are widespread throughout the world and have been increasing since the early 1990s partially because of ineffective pediculicides. In Argentina, the overuse of products containing pyrethroids has led to the development of resistant louse populations. Pyrethroid insecticides act on the nervous system affecting voltage-sensitive sodium channels. Three point mutations at the corresponding amino acid sequence positions M815I, T917I, and L920F in the voltage-gated sodium channel gene are responsible for contributing to knockdown resistance (kdr). The management of pyrethroid resistance requires either early detection or the characterization of the mechanisms involved in head louse populations. In the current study, we estimated the distribution of kdr alleles in 154 head lice from six geographical regions of Argentina. Pyrethroid resistance kdr alleles were found in high frequencies ranging from 67 to 100%. Of these, 131 (85.1%) were homozygous resistant, 13 (8.4%) were homozygous susceptible, and 10 (6.5%) were heterozygous. Exact tests for the Hardy-Weinberg equilibrium for each location showed that genotype frequencies differed significantly from expectation in four of the six sites studied. These results show that pyrethroid resistance is well established reaching an overall frequency of 88%, thus close to fixation. With 30 yr of pyrethroid-based pediculicides use in Argentina, kdr resistance has evolved rapidly among these head louse populations.